2016
DOI: 10.1016/j.expneurol.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing effects of RXR agonist bexarotene on aging-related synapse loss depend on neuronal LRP1

Abstract: Apolipoprotein E (apoE) plays a critical role in maintaining synaptic integrity by transporting cholesterol to neurons through the low-density lipoprotein receptor related protein-1 (LRP1). Bexarotene, a retinoid X receptor (RXR) agonist, has been reported to have potential beneficial effects on cognition by increasing brain apoE levels and lipidation. To investigate the effects of bexarotene on aging-related synapse loss and the contribution of neuronal LRP1 to the pathway, forebrain neuron-specific LRP1 knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 61 publications
0
35
1
1
Order By: Relevance
“…Previous evidence has suggested that RXR and its heterodimer partners are able to regulate the transcription of neuronal genes important for neurogenesis and neurite extension [6770], synaptic function [71], and neuronal survival [1]. A recent study from Sandoval-Hernandez et al reports that treatment of 3xTg-AD mice with LXR agonist GW3965 increases proliferation of neural precursors in the subgranular zone and rescues Aβ-induced deficits in long-term potentiation (LTP) in a protein-synthesis dependent manner [72].…”
Section: Lxrs In Cns Disordersmentioning
confidence: 99%
“…Previous evidence has suggested that RXR and its heterodimer partners are able to regulate the transcription of neuronal genes important for neurogenesis and neurite extension [6770], synaptic function [71], and neuronal survival [1]. A recent study from Sandoval-Hernandez et al reports that treatment of 3xTg-AD mice with LXR agonist GW3965 increases proliferation of neural precursors in the subgranular zone and rescues Aβ-induced deficits in long-term potentiation (LTP) in a protein-synthesis dependent manner [72].…”
Section: Lxrs In Cns Disordersmentioning
confidence: 99%
“…Bexarotene significantly slowed cognitive decline in an amyloid mouse model expressing human APOE ε 3 and APOE ε4 [121], and reversed the APOE ε4-induced cognitive and neuronal impairments in mice without amyloid background [99]. Age-dependent loss of synaptic proteins is also restored by bexarotene [102]. However, there are conflicting reports regarding the effects of bexarotene treatment on amyloid pathology in mouse models [101, 103, 105, 106, 121].…”
Section: Apoe-targeted Therapy For Admentioning
confidence: 99%
“…However, there are conflicting reports regarding the effects of bexarotene treatment on amyloid pathology in mouse models [101, 103, 105, 106, 121]. In addition, bexarotene-induced adverse side effects including hepatic failure have been reported [102, 104]. Furthermore, in a clinical study, four weeks of bexarotene treatment in AD patients did not reduce brain amyloid as measured by PET scans, but the sample size was notably small (ClinicalTrials.gov identifier NCT01782742) [122].…”
Section: Apoe-targeted Therapy For Admentioning
confidence: 99%
“…In this regard, it is important to emphasize that bexarotene treatment attenuated neuronal loss in the subiculum and cortex in 5xFAD mice, which correlated with significant increases in the levels of post‐synaptic marker PSD95 and the presynaptic marker synaptophysin (Mariani et al, ). Tachibana et al presented the ability of bexarotene to restore the levels of post‐synaptic proteins (PSD95, GluR1, and NR1) which were observed to be diminished with age and important in synaptic plasticity (Tachibana et al, ). RXR agonists were also shown to have therapeutic potential in reversing the age‐associated decreases in myelin debris removal and remyelination (Natrajan et al, ).…”
Section: Retinoid X Receptorsmentioning
confidence: 99%
“…Tachibana et al presented the ability of bexarotene to restore the levels of post-synaptic proteins (PSD95, GluR1, and NR1) which were observed to be diminished with age and important in synaptic plasticity (Tachibana et al, 2016). RXR agonists were also shown to have therapeutic potential in reversing the age-associated decreases in myelin debris removal and remyelination (Natrajan et al, 2015).…”
Section: Other Mechanismsmentioning
confidence: 99%